2008
DOI: 10.1254/jphs.08001fp
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Inhibits Rat Aortic Smooth Muscle Cell Proliferation Through the Induction of p27kip1

Abstract: Abstract. Diet is one of the most important factors that influence the risks for cardiovascular diseases. Genistein, an isoflavone found in soy, may benefit the cardiovascular system. Here, we investigated the effect of genistein on platelet-derived growth factor (PDGF)-BB-induced proliferation of primary cultured rat aortic smooth muscle cells (RASMCs). Genistein significantly inhibited 25 ng / ml PDGF-BB-induced RASMC proliferation and [ 3 H]-thymidine incorporation into DNA at 10, 20, and 40 μM. In accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…The study showed that dihydrodaidzein selectively inhibited neointimal proliferation, possibly by inhibiting VSMC migration and proliferation and/or enhancing endothelial proliferation and function [110]. Also, in rat aortic SMCs genistein inhibits PDGF-induced proliferation by blocking the progression from the G0/G1 to S phase of the cell cycle [111]. It has also been shown that TGF-β-stimulated clone-36, a matricellular protein induced by daidzein, inhibits human umbilical artery SMC proliferation and migration in vivo and in vitro , and causes accumulation of SMCs in G2 phase of the cell cycle [112].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that dihydrodaidzein selectively inhibited neointimal proliferation, possibly by inhibiting VSMC migration and proliferation and/or enhancing endothelial proliferation and function [110]. Also, in rat aortic SMCs genistein inhibits PDGF-induced proliferation by blocking the progression from the G0/G1 to S phase of the cell cycle [111]. It has also been shown that TGF-β-stimulated clone-36, a matricellular protein induced by daidzein, inhibits human umbilical artery SMC proliferation and migration in vivo and in vitro , and causes accumulation of SMCs in G2 phase of the cell cycle [112].…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] This raises an interesting question of pharmacology and cell biology as to the mechanism of the inhibitory action of (S)-[6]-gingerol. At this time we can only speculate on the mechanism of inhibition, based by analogy on the effect of genistein on PDGF-stimulated proliferation of VSMCs [41] and the inhibition of proteoglycan synthesis. [42,43] In this latter example, PDGF stimulation of VSMCs leads to PDGF receptor phosphorylation and, downstream, a fall in the levels of p27 kip1 as an obligatory step in cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…[42,43] In this latter example, PDGF stimulation of VSMCs leads to PDGF receptor phosphorylation and, downstream, a fall in the levels of p27 kip1 as an obligatory step in cell cycle progression. [41] Genistein inhibits proliferation by blocking the fall in p27 kip1 levels but it does not block PDGF receptor phosphorylation. Genistein blocks proteoglycan synthesis in human VSMCs without blocking PDGF-mediated PDGF receptor phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein is a small-molecule EGFR tyrosine kinase (TK) inhibitor, which can inhibit TK activation and subsequently lead to blockade of EGFR signaling pathway by competing with adenosine triphosphate (ATP) binding to the TK domain of the receptor, resulting in the suppression of cell proliferation and differentiation [12][13][14][15]. For this reason, EGFR inhibitors, such as genistein, always serve as agents for treating a variety of solid tumors.…”
Section: Introductionmentioning
confidence: 99%